Dealing with doping. A plea for better science, governance and education. Issue 2 (12th August 2021) - Heuberger, Jules A. A. C.; Henning, April; Cohen, Adam F.; Kayser, Bengt
Abstract : The creation of WADA contributed to harmonization of anti‐doping and changed doping behavior and prevalence in the past 22 years. However, the system has developed important deficiencies and limitations that are causing harm to sports, athletes and society. These issues are related to the lack of evidence for most substances on the Prohibited List for performance or negative health effects, a lack of transparency and accountability of governance and decision‐making by WADA and the extension of anti‐doping policies outside the field of professional sports. This article tries to identify these deficiencies and limitations and presents a plea for more science, better governance and more education. This should lead to a discussion for reform among stakeholders, which should cover support of a new Prohibited List by actual research and evidence and introduce better governance with accountable control bodies and regulation. Finally, comprehensive education for all stakeholders will be the basis of all future positive improvements.